ALTC Promoting Excellence Initiative : major themes identified in completed institutional project reports. - Nagy, Judy; Devlin, Marcia; Brooker, Miriam; Smeal, Georgia; Cummings, Rick; Mazzolini, Margaret; Lyubomirsky, Anna (Australian Learning and Teaching Council (ALTC), 2011)
Summary of key themes of completed PEI reports. The purpose of this project were twofold. The first is to distil and highlight the leadership challenges faced by the leaders and champions of the ALTC's Promoting Excellence Initiative (PEI) and to feature as exemplars those initiatives that have had the most positive impact within an institution. The project team contended that successful initiatives are contingent upon the contextual environment, formal leaders, others within the leadership hierarchy and the expectations of staff they are intended to motivate. The second purpose was to learn from and provide effective leverage for resources already expended by the ALTC in relation to the PEI. This project identified what has been implemented and embedded through the PEI, and examine to what extent initiatives have promoted institutional excellence and engagement in learning and teaching. In essence, the project undertook a benefit analysis of the PEI, while focusing on the leadership skills required to lead with, through and around formal hierarchical structures to achieve objectives.